2008
DOI: 10.1103/physreva.78.052326
|View full text |Cite
|
Sign up to set email alerts
|

Generalized parity measurements

Abstract: Measurements play an important role in quantum computing (QC), by either providing the nonlinearity required for two-qubit gates (linear optics QC), or by implementing a quantum algorithm using single-qubit measurements on a highly entangled initial state (cluster state QC). Parity measurements can be used as building blocks for preparing arbitrary stabilizer states, and, together with 1-qubit gates are universal for quantum computing. Here we generalize parity gates by using a higher dimensional (qudit) ancil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…We develop a full ancilla-mediated model of quantum computation based only on controlled displacement operators acting on an ancilla qudit. The previous work [30,31] on ancillary qudits can also be understood within this framework and we show that the computational advantages demonstrated in the qubus model can be transferred into this finite dimensional context.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…We develop a full ancilla-mediated model of quantum computation based only on controlled displacement operators acting on an ancilla qudit. The previous work [30,31] on ancillary qudits can also be understood within this framework and we show that the computational advantages demonstrated in the qubus model can be transferred into this finite dimensional context.…”
Section: Introductionmentioning
confidence: 77%
“…As this is a two-qubit entangling gate as long as xp = nd for any integer n this is universal for quantum computation on the register with the addition of single-qubit gates on the register. It has already been shown that there are computational advantages that can be gained from using ancillary qudits to aid a computational model [27,30,31]. We consider the generalized Toffoli gate which maps the basis states of n control and one target qubit to |q 1 ,q 2 .…”
Section: B the Computational Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest diversity of multipartite entangled states has been achieved so far by using the polarization degrees of freedom of photons, generated by spontaneous parametric down-conversion (SPDC) and subsequently fed into special arrangements of linear optical elements [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Although a large variety of different states can be produced by this technique, it usually suffers from the need of a particular experimental configuration for the generation of a particular entangled state [9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that parity meters provide a new realization of quantum computing [30,31] and are capable of building up many different types of entangled states [22,23,32]. Parity meters have also been recently been used to explore rapid two-party purification and enhanced entanglement generation using feedback control [33].…”
Section: Even Paritymentioning
confidence: 99%